2022
DOI: 10.1161/strokeaha.122.040233
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Stroke in Randomized Trials of COVID-19 Therapeutics: A Systematic Review and Meta-Analysis

Abstract: Background: COVID-19 has been frequently associated with an increased risk of thrombotic complications. There have also been reports of an increased likelihood of stroke, although its true incidence in patients with COVID-19 is currently unknown. Methods: Electronic databases PubMed and Scopus were searched from inception up to July 30, 2021 to identify randomized controlled studies in patients with confirmed COVID-19 undergoing one or more intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 118 publications
0
6
0
Order By: Relevance
“…Considering the methodological quality of AMSTAR-2 tool items, 15 [6,8,[14][15][16][17][18][19][20][21][22][23][24][25][26] and 1 [27] studies were rated as being of high and moderate quality, respectively. Overall, 16 [7,24,[28][29][30][31][32][33][34][35][36][37][38][39][40][41] and 12 [5,[42][43][44][45][46][47][48][49][50][51][52] studies were rated as being of low and critically low quality (online suppl. Material S3 Table 1).…”
Section: Study Identification and Characteristicsmentioning
confidence: 99%
“…Considering the methodological quality of AMSTAR-2 tool items, 15 [6,8,[14][15][16][17][18][19][20][21][22][23][24][25][26] and 1 [27] studies were rated as being of high and moderate quality, respectively. Overall, 16 [7,24,[28][29][30][31][32][33][34][35][36][37][38][39][40][41] and 12 [5,[42][43][44][45][46][47][48][49][50][51][52] studies were rated as being of low and critically low quality (online suppl. Material S3 Table 1).…”
Section: Study Identification and Characteristicsmentioning
confidence: 99%
“…Acute stroke has been commonly reported as a neurological complication, but the overall frequency in the covid-19 population is low (1.4%; 95% confidence interval 1.0 to 1.9) 111. A meta-analysis suggested that the absolute incidence of stroke was 0.168%, lower than previously estimated 112. The most common manifestation was acute ischemic stroke (87.4%); intracerebral hemorrhage was less common (11.6%) 111.…”
Section: Neurological Syndromesmentioning
confidence: 91%
“…The prevalence of AIS with COVID-19 was reported as 0.2–2.7% in previous publications, which is consistent with our prevalence data of 0.4% [ 3 , 8 , 9 , 17 ]. A recent systematic review and meta-analysis by Nagraj et al reviewed the incidence of stroke in randomized trials for COVID-19 therapeutics and included studies until 30 July 2021 [ 18 ]. This systematic review included 38,732 patients from inpatient and outpatient settings (65 patients with stroke) from 77 randomized studies, and all reported stroke events happened in the inpatient setting with an overall incidence of 0.18%.…”
Section: Discussionmentioning
confidence: 99%
“…They also concluded that there is a possibility of an association between the severity of the COVID-19 infection with the occurrence of stroke. Compared to prior studies, which have included smaller sample sizes [ 6 , 18 ], our study compares AIS outcomes in COVID-19 patients based on one of the largest cohorts of COVID-19 patients hospitalized in the United States in 2020. To our knowledge, our study is the largest study looking at the inpatient outcomes of patients hospitalized with AIS and COVID-19.…”
Section: Discussionmentioning
confidence: 99%